Comparative Effectiveness and Safety of Thulium Laser Enucleation and Holmium Laser Enucleation for BPH: Systematic Review and Meta-Analysis of Randomized Controlled Trials - Yuan Tang; Bo Xiong; Lin Yang; Changjian Zheng (Journal of Clinical Medicine, 2026)
Background: Holmium laser enucleation of the prostate (HoLEP) is a minimally invasive surgery for BPH. Thulium-based techniques (ThuLEP/ThuFLEP) are increasingly used for their cutting/coagulation benefits, but their comparative outcomes versus HoLEP remain uncertain. Methods: Our synthesis relied solely on RCT data comparing ThuLEP/ThuFLEP versus HoLEP for BPH. Eligible studies were RCTs directly comparing ThuLEP or ThuFLEP with HoLEP. Results: Eight RCTs involving 1196 patients were included. Compared with HoLEP, thulium laser enucleation demonstrated similar perioperative outcomes, with no statistically significant differences observed in operative time, enucleated tissue weight, hospital stay, or catheterization time. Postoperative hemoglobin decrease was comparable between the two groups (MD −0.34, 95% CI −0.69 to 0.01, p = 0.05). Subgroup analyses indicated that ThuLEP might be associated with potential advantages in postoperative hemoglobin decrease and transient urinary incontinence; however, these findings require cautious interpretation due to limited sample sizes and heterogeneity among studies. No significant differences were identified in postoperative complications or functional recovery outcomes. Conclusions: Current evidence from RCTs indicates that thulium laser enucleation techniques and HoLEP provide similar efficacy and safety outcomes for patients undergoing surgical treatment of BPH.